Enjeux et défis du développement international : Acteurs et champs d'action. Édition nouvelle et actualisée - Benhmade, Abdelhamid, 1988-; Haslam, Paul Alexander; Caouette, Dominique; Beaudet, Pierre, 1950- (Project Muse, 2019)
International development is a contested territory. As emergencies grow in number and scale, international aid is increasingly unable to respond to the desperate need arising from them. In spite of the objectives established by the United Nations in 2000, global poverty persists, and worse still, the gap between "North" and "South" is widening nearly everywhere. Meanwhile, the challenges posed by climate change have been turning everything upside down over the past century. Despite these tremendous strains, communities in the North and South are beginning to take matters into their own hands. They are reinventing development around key principles, such as respect for human diversity; the right to live with dignity; the organic bond between humans; non-human life; nature; the importance of participation; and a democracy that reaches beyond the narrow boundaries that currently confine it. This book brings together perspectives from diverse backgrounds to reflect on the "why" and the "how" of this critical situation. Contributors from around the world present initiatives and hypotheses aimed at restoring the world--and development--to the right side up.